Marcadores bioquímicos como apoyo al diagnóstico de síndrome metabólico en adultos. Prevalencia y factores de riesgo. Revisión sistemática - Gualán Sigcho, Nixon Alexander (2024)
The metabolic syndrome is the group of metabolic alterations, that included the increase of abdominal obesity hypertension, hypertriglyceridemia, hyperglycemia and HDL-C low; it turns important when makes the person able to develop diabetes and cardiovascular illness, first and fourth reason of death cause of no transmissible diseases’ world wide severally. To tackle this project, it was designing a systematic review to identify the prevalence, the biochemical markers as support of the diagnosis and risk factors associated to the metabolic syndrome in adults. For the study was used 24 papers to get the information obtained from data base as Scielo, PubMed, LILACS and Dialnet, from 2021. Worldwide the highest presence of metabolic syndrome was found in 47,6% in Iran and the lowest of 10.09% was in Burkina Faso, the biochemical markers used for the diagnosis are HDL-C, plasma glucose and tryglycerides, the risk factors that predispose to the adult population to develop the metabolic syndrome were age, sex, relatives’ backgrounds, physical activity, alcohol consumption, smoke habit, diet, sleep duration, depression, stress, live in urban areas, education, and income. In conclusion, this study gives value information about the metabolic syndrome, the highest and the lowest prevalence found, the most frequent biochemical markers and the risk factors associate to this metabolic syndrome these discoveries can help to adopt prevention strategies and help to avoid the development of the metabolic syndrome and its complications, also can help to the health personnel to take decision related to the metabolic syndrome